Validity and reliability of a handheld blood glucose monitor during exercise and an oral glucose tolerance test (Kinesiology, 2019)
The purpose of the present study was to examine the validity and reliability of the handheld Nova Max Plus blood glucose monitor during an oral glucose tolerance test and 60-minute bout of exercise. Thirty subjects (mean age±SD=22.3±1.9 years; body mass=77.6±14.2 kg) volunteered for an oral glucose tolerance test or 60-minute treadmill test. Blood glucose concentrations were measured from the fingertip at six time points during both tests. The reference method of blood glucose analysis was the Yellow Springs Instruments (YSI) 2300. Our results indicated that the blood glucose values provided by the Nova Max Plus were significantly (p